NUTRITIONAL HEALTH EDUCATION FOR NUTRITIONAL HEALTH EDUCATION FOR PUBLIC MOTHER "CARE FOR PUBLIC WOMEN REMAINING HEALTHY IN THE PANDEMIC TIME COVID 19" - ERNIAWATI, ERNIAWATI (PITIMAS: Journal of Community Engagement in Health, 2022)
Abstract Uterine involution is a change which is the process of returning the uterus or uterus and birth canal after the baby is born until it reaches a pre-pregnancy state that is influenced by mobilization, nutrition and postpartum exercise. Inadequate nutritional management during the postpartum period can cause problems. Lack of knowledge of postpartum mothers on the importance of nutrition will cause problems, both for the mother and the baby. Health education is needed to improve understanding of post partum mothers regarding nutrition during post partum. The purpose of this counseling is to provide health education about nutrition for postpartum mothers. This community service takes the form of 2 activities, namely health education on postpartum nutrition and postpartum exercise training. The health education methods used were lectures and questions and answers. Meanwhile, postpartum gymnastics training includes the correct role model of postpartum gymnastics techniques. The purpose of this Community Service is to provide knowledge to postpartum mothers about the importance of nutritional substances for their own health. Participants of health education and postpartum gymnastics training were 20 postpartum mothers. Community service activities were carried out for 1 day in the Hall of the Tahirah Al Baeti Midwifery Academy in Bulukumba. After participating in this activity, the participants understand and know the importance of nutrition during childbirth. Keywords: nutrition, childbirth, involution